Potensi Ekstrak Daun Sage (Salvia officinalis.L) sebagai anti-Streptococcus suis Penyebab Zoonotik Meningitis - Mitra Slipranata; Fajar Budi Lestari; Novra Arya Sandi; Siti Isrina Oktavia Salasia (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
The phenomenon of microbial resistance to an antibiotic or some kind of specific antibiotics (multi drugs resistance) greatly complicate the treatment process, one of which is Streptococcus suis (S. suis) which is known to cause meningitis in animals and humans. Today, with rising bacterial resistance to a wide rangeof antibiotics, it takes an effort to assess the potential medicinal plants as an antibiotic that is appropriate and safe. Sage (Salvia officinalis.L) is reported to have antibacterial and fungicidal effect. Phenolic acids such assalvin and ether monomethyl salvin which isolated from the sage thought to have antimicrobial activity against several bacterial strains. The purpose of this study was to prove the ability of sage leaf extract as an antibacterialagainst S. suis causes streptococcal meningitis in vitro. In-vitro method used in this research through a two-stage dilution test and the diffusion test on Mueller Hinton Agar (MHA). S. suis isolates (code 225) were tested in vitro against 8 levels sage leaf extract concentration, ie a concentration of 1%, 3% 5%, 7%, 10%, 20%, 40% and 60%. The results of the test obtained by minimum inhibitory concentrations (MICs) and minimum sage known to potentially inhibit the growth of S. suis.